Adaptation of Leishmania donovani to Cutaneous and Visceral Environments: in Vivo Selection and Proteomic Analysis - McCall, Laura-Isobel; Zhang, Wen-Wei; Dejgaard, Kurt; Atayde, Vanessa Diniz; Mazur, Alexander; Ranasinghe, Shalindra; Liu, Jing; Olivier, Martin; Nilsson, Tommy; Matlashewski, Greg (American Chemical Society Publications, 2015)
Leishmaniasis is a neglected tropical disease caused by Leishmania protozoa. Two main forms are found in the Old World, self-limited cutaneous leishmaniasis and potentially fatal visceral leishmaniasis, with parasite dissemination to liver, bone marrow, and spleen. The Leishmania donovani species complex is the causative agent of visceral leishmaniasis worldwide, but atypical L. donovani strains can cause cutaneous leishmaniasis. We hypothesized that L. donovani can adapt to survive in response to restrictions imposed by the host environment. To assess this, we performed in vivo selection in BALB/c mice with a cutaneous L. donovani clinical isolate to select for parasites with increased capacity to survive in visceral organs. We then performed whole cell proteomic analysis and compared this visceral-selected strain to the original cutaneous clinical isolate and to a visceral leishmaniasis clinical isolate. Overall, there were no major shifts in proteomic profiles; however, translation, biosynthetic processes, antioxidant protection, and signaling were elevated in visceral strains. Conversely, transport and trafficking were elevated in the cutaneous strain. Overall, these results provide new insight into the adaptability of Leishmania parasites to the host environment and on the factors that mediate their ability to survive in different organs.
Keywords: visceral leishmaniasis; proteomic analysis; virulence; pathogenesis